x squared plus 5
1 over x2 - 4 is the multiplicative inverse of x2 minus four 1/x2 - 4
(x - 5)(x + 4)
X squared is not an inverse function; it is a quadratic function.
(x + 2)(x - 4)
x = ? 42 = x squared minus x
x(x + 3)(x - 4)
3x2 - 11x - 4 = (x-4)(3 x + 1)
x2 - 4= (x+2) (x-2)
x3 + 4x2 - 16x - 64 = (x + 4)(x + 4)(x - 4).
4(x - 1)(x + 1)
By factoring I get x-3 divided by x+3
It is x^2 -x -12 is (x+3)(x-4) when factored
x2-4x-165 = (x-15)(x+11) when factored
It is not clear what you want to solve for.
It is the difference of squares. (x-4) and (x+4) <--- answer
-22 - -22
x^2-4x/x^2-6x+8 = x(x-4)/(x-2)(x-4) = x/(x-2)
x2-5x-36 = (x-9)(x+4) when factored
(x - 4)(3x + 5)
To find the inverse of a function, you replace x with y and y with x. Here, y=2x-4 would become x=2y-4. Now, we solve for y. 2y=x+4. y=(x/2)+4, and that is the inverse equation.